Effects of an active pockmark field on the distribution of heavy metals of surficial sediments in the Gulf of Patras, Greece - RAVASOPOULOS, J.; PAPATHEODOROU, G.; KAPOLOS, J. (Bulletin of the Geological Society of Greece, 2018)
Factor analysis carried out in thirteen sediment cores, collected from an active pockmark field area in the eastern part of the Gulf of Patras, discriminated a domestic sewage pollution factor, the Mn/Fe oxides and the carbonate sedimentation. The increased content in sand, the low C content as well as the lack of C /heavy org org" J metals association follow a specific NW-SE transect in the centre of the surveyed pockmark field, suggesting pockmarks activity. This seems to control sedimentation and heavy metals distributions.